Infark Ventrikel Kanan dengan Blok Atrioventrikular: Laporan Kasus dengan Tinjauan Pustaka - Dalimunthe, Naomi Niari; Hasan, Refli; Ahmad, Herwindo; Isnanta, Rahmad; Realsyah, T; Safri, Zainal (UI Scholars Hub, 2024)
Inferior myocardial infarction is frequently accompanied by right ventricular infarction. This report presents two cases of right ventricular infarction accompanied by hemodynamic disorder and atrioventricular block complications. These patients were diagnosed with right ventricular infarction based on history, clinical presentations, and electrocardiography findings. The management approach for these patients involved optimizing volume and fluid status, using temporary pacemakers, and urgent percutaneous coronary intervention. This report highlights the need to promptly identify right ventricular involvement in inferior myocardial infarction, as the treatment strategies for right ventricular infarction are different from left ventricular infarction.